PELAKSANAAN RESORATIVE JUSTICE SYSTEM OLEH POLRI UNTUK MEWUJUDKAN TUJUAN HUKUM DI INDONESIA - Bakri, Nofrizal Bakri; Padri, Padrisan Jamba (LPPM Universitas Putera Batam, 2024)
In order to realize justice, usefulness and legal certainty, which is the hope of the community, the National Police has opened up opportunities to resolve criminal cases through a restorative justice mechanism, Republic of Indonesia State Police Regulation Number 8 of 2021 concerning the handling of restorative criminal acts, the State Police of the Republic of Indonesia, (polri) as part of the Integrated Criminal Justice System has a very important role in enforcing criminal law, implementing Restorative Justice to realize legal objectives in Indonesia. The National Police is authorized by Law Number. 2 of 2002 concerning the Indonesian National Police to formulate a new concept in criminal law enforcement that accommodates the norms and values ​​that apply in society as a solution while providing legal certainty, especially for the benefit and sense of justice of the community.